Additives for photosynthetic bacteria wastewater treatment: Latest developments and future prospects. (September 2019) - Chen, Yang; Yang, Anqi; Meng, Fan; Zhang, Guangming
Abstract: Photosynthetic bacteria wastewater treatment is a new technology which can simultaneously remove pollutants from wastewater and produce high-value substances. However, this technology is restricted by the treatment efficiency and yield of high-value substances. In recent years, using additives as an enhancement approach has drawn more and more attention. Additives can effectively improve the treatment efficiency and production of these high-value substances with low energy consumption and easy operation. This review summarizes and evaluates the recent advances in additives for photosynthetic bacteria wastewater treatment. According to their properties, these additives are divided into four categories including trace elements, organic additives, biostimulation, and energy. The functional mechanisms and promoting performance of different additives were presented in details. Meanwhile, the optimal additive dosage and the link between wastewater composition and appropriate additives were discussed. Finally, based on critical analysis, remained challenges and barriers that need to be overcome in the future were proposed. Graphical abstract: Unlabelled Image Highlights: Various additives in photosynthetic bacteria wastewater treatment were summarized. Fe 2+ and Mg 2+ were the most popular additives that constituted 40% of total. Microorganism additives increased COD removal by 178%. Mg 2+ increased biomass production by 70%. Fe 2+ increased production of high-value substances by 60%–240%.